Evaluating the impact of contrast agents on micro and nano mechanics of soft-to-hard tissue interface - Atousa Moayedi; Katerina Karali; Markus Boese; Jurgita Zekonyte; Jovana Radulovic; Gordon Blunn (Scientific Reports)
Abstract Transmission of strain across the tendon-bone interface otherwise known as the enthesis, is crucial to the movement of the skeleton. Imaging the inner structure and understanding the way that strain is transmitted across this interface is crucial to understanding the way it responds to load, how it becomes injured through trauma and how intervention and materials can be used to repair the enthesis after injury. Micro-CT imaging and digital volume correlation (DVC) have been widely used for musculoskeletal biomechanics analysis. However, there are limitations for soft tissue visualization. Contrast agents (CA) are used to address this, but understanding their potential effects is essential to ensure accurate and reliable characterization of musculoskeletal tissues biomechanics. In this research, four different contrast-enhanced staining solutions (CESS) including Iodine (I2) in Dulbecco’s modified eagle medium (DMEM), Phosphotungstic acid (PTA) in deionized water, PTA in ethanol, and Mercury II Chloride (HgCl2) in deionized water were used to visualize the tendon-to-bone interface using a combination of high resolution in-situ micro-computed tomography (micro-CT) imaging. The imaging was combined with DVC, nanoindentation, and quantitative 3D structural analysis to evaluate the effects of the CESS on the mechanical properties of the enthesis. The findings revealed significant alterations in mechanical behaviour and structural features of soft-to-hard tissue interfaces treated by CESS. The findings suggest that I₂ in DMEM provides a better balance between visualization and mechanical analysis. However, none of the CESSs completely preserved both structural and mechanical integrity.